Money, Output, and the Expected Real Interest Rate - Diba, Behzad T.; Oh, Seonghwan (The Review of Economics and Statistics, 1991)
This paper tests the exclusion of lagged growth rates of money and output from regression equations, with serially correlated disturbances, for the expected real interest rate. The authors empirical approach is an extension of the empirical strategies of Eugene F. Fama (1975) and Frederic S. Mishkin (1981)–which invoke the orthogonality of the inflation forecast error to predetermined regressors under the maintained hypothesis of rational expectations. They discuss the implications of their tests for simple real-business-cycle models. Copyright 1991 by MIT Press.